Application of the endogenous CRISPR-Cas type I-D system for genetic engineering in the thermoacidophilic archaeon Sulfolobus acidocaldarius - Bost, Jan; Recalde, Alejandra; Waßmer, Bianca; Wagner, Alexander; Siebers, Bettina; Albers, Sonja-Verena (Frontiers in Microbiology, 2023)
CRISPR (clustered regularly interspaced short palindromic repeats)-Cas systems are widely distributed among bacteria and archaea. In this study, we demonstrate the successful utilization of the type I-D CRISPR-Cas system for genetic engineering in the thermoacidophilic archaeon Sulfolobus acidocaldarius. Given its extreme growth conditions characterized by a temperature of 75°C and pH 3, an uracil auxotrophic selection system was previously established, providing a basis for our investigations. We developed a novel plasmid specifically designed for genome editing, which incorporates a mini-CRISPR array that can be induced using xylose, resulting in targeted DNA cleavage. Additionally, we integrated a gene encoding the β-galactosidase of Saccharolobus solfataricus into the plasmid, enabling blue-white screening and facilitating the mutant screening process. Through the introduction of donor DNA containing genomic modifications into the plasmid, we successfully generated deletion mutants and point mutations in the genome of S. acidocaldarius. Exploiting the PAM (protospacer adjacent motif) dependence of type I systems, we experimentally confirmed the functionality of three different PAMs (CCA, GTA, and TCA) through a self-targeting assessment assay and the gene deletion of upsE. Our findings elucidate the application of the endogenous Type I-D CRISPR-Cas system for genetic engineering in S. acidocaldarius, thus expanding its genetic toolbox.